Evolución de la publicidad en la red social Facebook en la ciudad de Babahoyo - Cruz Cerezo, Leyberth Joel (2022)
The subject of study in this case is "Evolution of advertising on the social network Facebook in the city of Babahoyo", it is carried out in order to know how the digital transformation of the social network Facebook has been for companies to advertise products or services and can reach the target audience and have the most interaction with the followers. The city of Babahoyo has been characterized by launching enterprises that help the economy of the canton, managing to employ directly and indirectly, but not without first making each of them known through social networks. The methodology applied is the quantitative method, with the interview technique applied to a survey of several business owners in the city of Babahoyo to obtain true results based on the applied questionnaire.